Intervention for improvement the diet and physical activity of children and adolescents in Poland - Katarzyna Wolnicka; Jadwiga Charzewska; Anna Taraszewska; Renata Czarniecka; Joanna Jaczewska-Schuetz; Natalia Bieńko; Elżbieta Olszewska; Bożena Wajszczyk; Mirosław Jarosz (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. The effects of a two-year educational Programme "Keep Balance" addressed to children and adolescents have been evaluated. Its purpose has been to implement the rules of proper nutrition and increasing the level of physical activity on the population level. Objective. The main objective of the evaluation was an indication if, after two years of programme activities, outcome indicators have been achieved. Material and methods. Approximately 400,000 pupils/students from 1600 educational units from the territory of the whole country have been included in the education programme. The efficiency evaluation has been carried out in a sample of n = 1506 pupils/students in the interventional group and n = 1589 in the control group. Education has been addressed to the entire school environment, pupils, students, parents, teachers, headmasters, and the local community. The survey methodology, body weight and height measurements, the BMI index, and EUROFIT physical fitness tests have been used to assess the effects of the education programme in the scope of knowledge and nutritional behaviour regarding physical activity. There were assumed outcome indicators. The certification of schools/kindergartens with "The Certificate of a School/Kindergarten Friendly to Nutrition and Physical Activity" has been used to evaluate the activation of school environments. Results. There was an improvement achieved over the assumed target points in the level of knowledge of pupils/students in the scope of nutrition and the role of physical activity, in the changes of nutritional habits, and in the results of physical fitness tests. There were achieved 20% increase in knowledge in the scope of nutrition and 5% increase in physical activity. There have been changes in the frequency in the consumption of the first breakfast before going to school (by 25% among the younger ones and by 17% among the older ones), an increase in the consumption of bottled water by 49% and reduction of sweet drinks by 19%. The percentage of the pupils/students consuming the recommended 5 meals increased by 33%. Physical fitness indicators were achieved over assumed 5% increase in the individual exercise tests. The Certificate was obtained after meeting the criteria and documenting the durability of the changes by 65% of 1600 educational units included in the Programme. A decrease in the frequency of overweight and obesity occurrence in the whole intervention sample by 1% was obtained; it was greater (but statistically insignificant) among younger students by 3.3% in comparison to the older ones where there was an increase of 1%. Conclusions. Summing up all achieved results the educational programme "Keep Balance" implemented on the population level aimed at children and adolescents has turned out to be effective and deserves to be continued after minor adjustments. Many positive changes have been identified as well as those that ought to be improved. Comprehensively included education and sometimes small changes in much of nutritional and physical behaviour have influenced the reduction of the percentage of pupils/students with excessive body weight, despite the fact that the average BMI has basically remained on the same level.